Search
Ask a question
0

Solve by the square root property. (-x^2+1)^2 = 4

how do i solve this? 

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Sabreena M. | Patient, Eager-to-help Math/Science TutorPatient, Eager-to-help Math/Science Tuto...
4.9 4.9 (266 lesson ratings) (266)
0
Check Marked as Best Answer
By the square root property, the first step is to square root both sides, giving us: 
 
-x^2 + 1 = 2   OR   -x^2 + 1 = - 2
 
Solving for x in the first equations gives us -x^2 = 1, so x^2 = - 1. This is impossible unless we are solving over complex numbers. If we are, then x = i, - i. 
 
Now let's turn to the second equation. -x^2 = - 3, so x^2 = 3, and x = √3 or - √3.